Development of public science and technology organizations with learning organization approach - Tu Thao Huong Giang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Organizational learning is a topic of interest to many researchers and managers in organizations. A lot of questions about this topic have been raised as to whether an organization can learn or not? How will the organization learn? How does it relate to individual learning in the organization? In recent times, many related theoretical schools have been published to clarify the nature of organizational learning. This study was carried out with the aim of clarifying the nature of organizational learning process and analyzing the learning organization model in typical S&T organizations in universities in Vietnam. On that basis, recommendations are made in the development of science and technology organizations in the direction of learning organizations. Maximize knowledge resources to create outstanding competitive advantages based on organizational learning results. Code: 23021301